Review of Islamic Psychology: Building Correlations of Religious Maturity in Islamic Education - Wantini, Wantini; Sulastri, Sulastri; Mahmudah, Kharisma Noor Latifatul; Sulastri , Sulastri (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
The study of Islamic psychology is a field that is increasingly receiving widespread attention in the context of Islamic education. An in-depth understanding of how the principles of Islamic psychology can be applied in educational contexts, especially in building spiritual and religious maturity, is a major focus in this discussion. This study used the literature review method to investigate the relationship between Islamic psychology and Islamic education, particularly in the context of building religious maturity. The primary sources used consisted of original documents such as scientific journals, textbooks, research reports, and other official documents. Meanwhile, secondary sources included review articles, reference books, and reviews that discuss and analyze findings from primary sources. The results of this research showed the correlation between religious maturity and Islamic education, as outlined in the Allport criteria, highlighting a holistic approach to student development, integrating spiritual values with educational principles. By fostering good differentiation, motivation in a dynamic religion, and a comprehensive outlook on life, educators empower students to navigate their identity while embracing moral and academic growth. In the end, this synergy between religious maturity and education will give birth to individuals who are not only academically capable but also moral and socially minded.